Multi-stakeholder partnerships in Danish development policy: Poverty reduction, sustainable development and global public goods - Poul Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2014)
The world faces a multitude of global problems, on top of the need for poverty eradication. Climate change, natural disasters, state collapse, illicit capital flows, refugees and increasing inequality present new challenges to the international community. They require joint action for the provision of global public goods (GPGs). International multi-stakeholder partnerships (MSPs) have arisen as institutions of development cooperation in health, environment, human rights etc., because of the need to mobilize public and private actors and resources beyond official development assistance (ODA). However, MSPs are still dominated by the North, i.e. donor governments, international NGOs and organizations. MSPs are even opposed by governments of developing countries for their lack of democratic accountability. Through fragmentation, MSPs may have undermined the effectiveness and legitimacy of international development cooperation. Despite their promise of innovative financing and resource mobilization, most development oriented MSPs remain dependent on ODA. [...]
Keywords: 300; Inequality and poverty; Development policies and practice; Danish and European foreign policies